An Artistic Image Fusion Method with Improved Cartoon-Texture Decomposition - Zhou Meng (Advances in Multimedia)
When the art images are restored by the virtual restoration method, there are problems such as insufficient clarity and more noise in the reference image. An improved cartoon-texture decomposition method for art image fusion is proposed. The nonlinear local total variation component is used as the indicator function of image decomposition to obtain the image cartoon structure component and texture oscillation component. According to the oscillation component’s strong repetitiveness and structural directionality, the image texture part is filtered by combining the improved directional diffusion algorithm. Using the sparse coefficients of the fused cartoon component and the sparse coefficients of the texture component, the cartoon and texture of the image is inverse transformed and weighted and summed to obtain the recovered image after fusion. The experimental results show that this paper has a good effect after image fusion, and the recovered clarity is higher, which can better express the basic information of the source image; compared with several decomposition fusion methods commonly used at present, this paper has better recovery performance and detail processing ability and preserves the edge information of essential details in the image while filtering and denoising and is more excellent in objective performance evaluation indexes such as PSNR and SSIM. It can be used as a reference basis in the restoration process of art images.